Karakteristik demografi, sosial dan ekonomi sumber daya pemuda Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Abstract The productivity of youth must be increased in the development process of Indonesia. According to the 1990 population census, there are 50.7 million youths (people at the age between 15-29 years). Out of that number, only 52.1 percent who have directly participated in the development process, because their main activities are working. Of the rest, 20.6 percent took care of houses